2014
DOI: 10.1098/rstb.2013.0432
|View full text |Cite|
|
Sign up to set email alerts
|

Heritable strategies for controlling insect vectors of disease

Abstract: Mosquito-borne diseases are causing a substantial burden of mortality, morbidity and economic loss in many parts of the world, despite current control efforts, and new complementary approaches to controlling these diseases are needed. One promising class of new interventions under development involves the heritable modification of the mosquito by insertion of novel genes into the nucleus or of Wolbachia endosymbionts into the cytoplasm. Once released into a target population, these modifications can act to red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
201
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(201 citation statements)
references
References 109 publications
0
201
0
Order By: Relevance
“…With few exceptions (Hoffmann et al 2011), the practicality of such introductions has been limited by the lack of a means to ensure the spread of the engineered genetic material through a population. In a recent article, Gantz and Bier (2015) describe the mutagenic chain reaction (MCR), an approach that employs the CRISPR/Cas9 system to drive a mutation to high frequency in a population, making gene replacement at the population level practical for any species that can be made to accept a transgene in the laboratory.There is, in fact, an extensive literature on "gene drive" systems that can transform entire populations (reviewed in Sinkins and Gould 2006, Gould 2008, and Burt 2014 and going back to Curtis 1968and Foster et al 1972. The work of Burt and colleagues (Burt 2003;Deredec et al 2008;North et al 2013) considering the population genetics of homing endonucleases as a means to transform entire populations is particularly relevant, and much of what we describe below is a specific application of the general principles developed earlier and applied to MCR.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With few exceptions (Hoffmann et al 2011), the practicality of such introductions has been limited by the lack of a means to ensure the spread of the engineered genetic material through a population. In a recent article, Gantz and Bier (2015) describe the mutagenic chain reaction (MCR), an approach that employs the CRISPR/Cas9 system to drive a mutation to high frequency in a population, making gene replacement at the population level practical for any species that can be made to accept a transgene in the laboratory.There is, in fact, an extensive literature on "gene drive" systems that can transform entire populations (reviewed in Sinkins and Gould 2006, Gould 2008, and Burt 2014 and going back to Curtis 1968and Foster et al 1972. The work of Burt and colleagues (Burt 2003;Deredec et al 2008;North et al 2013) considering the population genetics of homing endonucleases as a means to transform entire populations is particularly relevant, and much of what we describe below is a specific application of the general principles developed earlier and applied to MCR.…”
mentioning
confidence: 99%
“…There is, in fact, an extensive literature on "gene drive" systems that can transform entire populations (reviewed in Sinkins and Gould 2006, Gould 2008, and Burt 2014 and going back to Curtis 1968and Foster et al 1972. The work of Burt and colleagues (Burt 2003;Deredec et al 2008;North et al 2013) considering the population genetics of homing endonucleases as a means to transform entire populations is particularly relevant, and much of what we describe below is a specific application of the general principles developed earlier and applied to MCR.…”
mentioning
confidence: 99%
“…One method currently under development entails genetic modification of the mosquito to bias the population sex ratio toward males (which do not bite), with the goal of local population reduction or elimination (15)(16)(17). Modeling has shown that the most efficient means toward this end is the engineering of a driving Y chromosome (18).…”
mentioning
confidence: 99%
“…Heritable genetic ‘sterility’ is not the only genetics‐based method being developed to control insect populations (Alphey, 2014; Burt, 2014). Recent advances in genetic modification have focussed on techniques of gene and genome editing.…”
Section: Gene Editingmentioning
confidence: 99%